CGIAR-ISEAL Scoping Study: State of gender integration among ISEAL community members in the agri-food sector - Morgan, Miranda (Bioversity International and the International Center for Tropical Agriculture, 2023)
Voluntary Sustainability Systems (VSS) can play an important role in reducing persistent gender inequalities and supporting women’s empowerment to achieve more just and resilient agri-food systems. However, research indicates that gender equality impacts have been minimal given few VSS have taken a strategic approach to addressing gender equality and there has been a failure to address the structural causes of gender equality in global supply chains. In order to support sustainability standards in their efforts to advance gender equality, a scoping study was recently conducted to understand the state of gender integration among VSS that are members of ISEAL (a global membership organization for credible sustainability standards). The study aimed to: explore how ISEAL members seek to enhance gender equality and women’s empowerment, with a focus on schemes in the agri-food sector; identify enabling factors and challenges for enhancing gender equality and promoting women’s rights and empowerment through ISEAL members’ systems; and consider opportunities for learning and collaboration to advance gender equality through VSS.